TMPRSS12 Functions in Meiosis and Spermiogenesis and Is Required for Male Fertility in Mice - Zhang, Jingjing; Zhou, Xinli; Wan, Danyang; Yu, Li; Chen, Xu; Yan, Tong; Wu, Zhu; Zheng, Meimei; Zhu, Feng; Zhu, Hui (Frontiers in Cell and Developmental Biology, 2022)
Serine proteases are involved in many physiological activities as initiators of proteolytic cascades, and some members have been reported to play roles in male reproduction. Transmembrane serine protease 12 (TMPRSS12) has been shown to regulate sperm motility and uterotubal junction migration in mice, but its role in the testis remains unknown. In this study, we verified that TMPRSS12 was expressed in the spermatocytes and spermatids of testis and the acrosome of sperm. Mice deficient in Tmprss12 exhibited male sterility. In meiosis, TMPRSS12 was demonstrated to regulate synapsis and double-strand break repair; spermatocytes of Tmprss12−/− mice underwent impaired meiosis and subsequent apoptosis, resulting in reduced sperm counts. During spermiogenesis, TMPRSS12 was found to function in the development of mitochondria; abnormal mitochondrial structure in Tmprss12−/− sperm led to reduced availability of ATP, impacting sperm motility. The differential protein expression profiles of testes in Tmprss12−/− and wild-type mice and further molecule identification revealed potential targets of TMPRSS12 related to meiosis and mitochondrial function. Besides, TMPRSS12 was also found to be involved in a series of sperm functions, including capacitation, acrosome reaction and sperm-egg interaction. These data imply that TMPRSS12 plays a role in multiple aspects of male reproduction.